A Conceptual Framework for User Acceptance of Islamic Accounting Information Systems: Integrating UTAUT and Maqāṣid al-Sharī‘ah Orientation - Praja Hadi Saputra; Noor Riefma Hidayah (Jurnal Akuntansi dan Keuangan Islam, 2026)
Digital transformation in the Islamic finance sector is driving the increasing adoption of Islamic Accounting Information Systems (IAIS) as an important instrument to ensure transparency, accountability, and compliance with sharia principles. Although the Unified Theory of Acceptance and Use of Technology (UTAUT) has been widely used to explain the adoption behavior of information systems, the model tends to be value-neutral and has not fully captured the normative dimensions inherent in sharia-based accounting systems. This article aims to develop a conceptual framework for the acceptance of value-based technologies in Islamic accounting by integrating the Maqāṣid al-Sharī'ah Orientation (MSO) into the UTAUT model. Conceptually, the orientation of maqāṣid represents the extent to which the use of IAIS supports the fundamental goals of sharia, such as justice, protection of property (ḥifẓ al-māl), transparency, and moral responsibility. This integration results in a Technology Acceptance Model (TAM) not only explain the actual intentions and use of the system based on performance and ease-of-use expectations but also considers the internalization of sharia values as a determinant of user behavior. The main theoretical contribution of this research is the development of a value-based technology acceptance framework in the Islamic accounting literature. In practical terms, the proposed model has implications for system developers, regulators, and Islamic financial institutions in designing an efficient IAIS aligned with sharia objectives.Transformasi digital dalam sektor keuangan Islam mendorong meningkatnya adopsi Islamic Accounting Information Systems (IAIS) sebagai instrumen penting untuk memastikan transparansi, akuntabilitas, dan kepatuhan terhadap prinsip syariah. Meskipun Unified Theory of Acceptance and Use of Technology (UTAUT) telah banyak digunakan untuk menjelaskan perilaku adopsi sistem informasi, model tersebut cenderung bersifat value-neutral dan belum sepenuhnya menangkap dimensi normatif yang melekat dalam sistem akuntansi berbasis syariah. Artikel ini bertujuan mengembangkan kerangka konseptual penerimaan teknologi berbasis nilai dalam konteks akuntansi Islam dengan mengintegrasikan Maqāṣid al-Sharī'ah Orientation (MSO) ke dalam model UTAUT. Secara konseptual, orientasi maqāṣid merepresentasikan sejauh mana penggunaan IAIS mendukung tujuan fundamental syariah, seperti keadilan, perlindungan harta (ḥifẓ al-māl), transparansi, dan tanggung jawab moral. Integrasi ini menghasilkan model penerimaan teknologi yang tidak hanya menjelaskan niat dan penggunaan aktual sistem berdasarkan ekspektasi kinerja dan kemudahan penggunaan, tetapi juga mempertimbangkan internalisasi nilai-nilai syariah sebagai determinan perilaku pengguna. Kontribusi teoretis utama penelitian ini adalah pengembangan kerangka value-based technology acceptance dalam literatur akuntansi Islam. Secara praktis, model yang diusulkan memberikan implikasi bagi pengembang sistem, regulator, dan lembaga keuangan Islam dalam merancang IAIS yang efisien sekaligus selaras dengan tujuan syariah.